2016
DOI: 10.1016/j.yjmcc.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Moderate intensity exercise prevents diabetic cardiomyopathy associated contractile dysfunction through restoration of mitochondrial function and connexin 43 levels in db/db mice

Abstract: Aims Although the cardiovascular benefits of exercise are well known, exercise induced effects and mechanisms in prevention of cardiomyopathy are less clear during obesity associated type-2 diabetes. The current study assessed the impact of moderate intensity exercise on diabetic cardiomyopathy by examining cardiac function and structure and mitochondrial function. Methods Obese-diabetic (db/db), and lean control (db/+) mice, were subjected to a 5 week, 300m run on a tread-mill for 5 days/ week at the speeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 42 publications
1
76
0
Order By: Relevance
“…However, exercise training, by improving insulin sensitivity in the cells, led to a significant decrease in insulin resistance and glucose levels in rats. Moreover, it has recently been shown that exercise inhibits the reduction of the Mfn2/Drp1 ratio in the heart tissue of db/db mice and also reduces cytochrome c leakage (Veeranki et al, 2016). Other studies have also shown that exercise can reduce the expression of Drp1 and increase the expression of Mfn1 and Mfn2 (Fealy, Mulya, Lai, & Kirwan, 2014).…”
Section: Creased the Results Of Various Studies Have Shown That Thementioning
confidence: 98%
See 1 more Smart Citation
“…However, exercise training, by improving insulin sensitivity in the cells, led to a significant decrease in insulin resistance and glucose levels in rats. Moreover, it has recently been shown that exercise inhibits the reduction of the Mfn2/Drp1 ratio in the heart tissue of db/db mice and also reduces cytochrome c leakage (Veeranki et al, 2016). Other studies have also shown that exercise can reduce the expression of Drp1 and increase the expression of Mfn1 and Mfn2 (Fealy, Mulya, Lai, & Kirwan, 2014).…”
Section: Creased the Results Of Various Studies Have Shown That Thementioning
confidence: 98%
“…Other studies have also shown that exercise can reduce the expression of Drp1 and increase the expression of Mfn1 and Mfn2 (Fealy, Mulya, Lai, & Kirwan, 2014). Moreover, it has recently been shown that exercise inhibits the reduction of the Mfn2/Drp1 ratio in the heart tissue of db/db mice and also reduces cytochrome c leakage (Veeranki et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, although imbalanced mitochondrial dynamics such as inhibited mitochondrial fusion or excessive mitochondrial fission is common in the hearts at different diabetic conditions, the fission/fusion proteins seem to be differently affected. It has been showed that Drp1 was significantly elevated in the hearts of type 2 diabetic d b /d b mice, whereas reduced protein expression of Mfn1 was observed in cardiac tissues from type 2 diabetic patients . The differences might be due to the differential microenvironment enveloping cardiac myocytes at different diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…250 Similarly, in a separate study 5 weeks of MIT on a treadmill lowered fibrosis and improved ATP levels in the hearts of db/db mice at 4 months of age, alongside improved oxygen consumption rates and improved contractile function in isolated cardiomyocytes. 251 In addition to effects on mitochondrial content and respiratory capacity, exercise may also influence mitochondrial dynamics, with decreased expression of DRP1 relative to that of the mitochondrial fusion factor Mfn1 seen following exercise in db/db mice. 251 The protective effects of exercise may be more limited in the older diabetic heart, however.…”
Section: Of 26mentioning
confidence: 99%
“…251 In addition to effects on mitochondrial content and respiratory capacity, exercise may also influence mitochondrial dynamics, with decreased expression of DRP1 relative to that of the mitochondrial fusion factor Mfn1 seen following exercise in db/db mice. 251 The protective effects of exercise may be more limited in the older diabetic heart, however. In 8-month-old db/db mice, 3 weeks of endurance training resulted in increased myocardial expression of PGC-1α alongside increased mtDNA density, but decreased ETS complex expression and increased mitochondrial fission, which the authors attributed to increased oxidative stress following exercise in older diabetic hearts.…”
Section: Of 26mentioning
confidence: 99%